The Influence of Word of Mouth and Price on the Decision to Purchase a Used Car at the Giat Motor Palembang Showroom - Wulandary, Ayu; Naruliza, Esty; Aryanti, Rahmi (Journal of Management, Economic, and Accounting, 2025)
Car sales in Indonesia continue to increase, including at the Giat Motor Palembang Showroom. One of the factors influencing consumer purchasing decisions is word of mouth and price. Word of mouth is a form of indirect promotion through consumer recommendations, while price is the value paid to obtain a product or service. This study aims to analyze the simultaneous and partial effects of word of mouth and price on car purchasing decisions. This study uses a quantitative method with multiple linear regression analysis. The population in this study consists of consumers who have purchased cars at the Giat Motor Palembang Showroom, with a sample of 88 respondents obtained through the distribution of questionnaires. The testing was conducted through validity and reliability tests, classical assumption tests, and hypothesis testing. The results of the study indicate that word of mouth and price simultaneously have a significant influence on the decision to purchase a used car. The coefficient of determination shows that 48.9% of purchasing decisions can be explained by these two variables, while the remainder is influenced by other factors. Partially, both also have a positive and significant influence on purchasing decisions. Thus, the hypotheses in this study are accepted.